Power Dressing and its Importance in Modern Democracy - Mansiben R Patel; Dr. Catherine Amoroso Leslie (Undergraduate Research Journal for the Human Sciences, 2023)
This research aimed to study the significance of Power Dressing in a modern democracy, by exploring the dynamics of clothing concerning the power it portrays for women holding influential positions in public office in a variety of countries throughout the world. This research accomplished its motive by collecting, reviewing, and analyzing scholarly articles, academic journals, newspapers, and current events which formed the foundation for data collection using a survey developed by the researchers. The analysis provided a platform for procuring knowledge of the association between Fashion and Politics, the concept of Women’s Power Dressing, and its significance in a modern democracy from an international perspective. With the changing dynamics of society, this study forms the base for a better understanding of the intersection of fashion, gender, and the latest events happening worldwide.
Keywords: Power Dressing; Gender; Cultural; Feminism; Politics; Individuality; Evolution